2019
DOI: 10.1155/2019/6527638
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide Inhibits Preformed Fibril-Induced Microglial Activation by Targeting the MicroRNA155-5p/SHIP1 Pathway

Abstract: Evidence suggests that various forms of α-synuclein- (αSyn-) mediated microglial activation are associated with the progression of Parkinson’s disease. MicroRNA-155-5p (miR155-5p) is one of the most important microRNAs and enables a robust inflammatory response. Triptolide (T10) is a natural anti-inflammatory component, isolated from a traditional Chinese herb. The objective of the current study was to identify the role and potential regulatory mechanism of T10 in αSyn-induced microglial activation via the miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…PI3K/Akt pathway is known to play important roles in controlling all these steps (86)(87)(88)(89). The potential targets of miR-155-5p includes PTEN (90) and SHIP1 (91), both of which negatively regulate PI3K/Akt signaling pathway (90,92). Given that miR-935/INPP4A axis could also regulate PI3K/Akt pathway, it is conceivable that targeting both miR-935 and miR-155-5p may lead to better outcomes in OSCC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt pathway is known to play important roles in controlling all these steps (86)(87)(88)(89). The potential targets of miR-155-5p includes PTEN (90) and SHIP1 (91), both of which negatively regulate PI3K/Akt signaling pathway (90,92). Given that miR-935/INPP4A axis could also regulate PI3K/Akt pathway, it is conceivable that targeting both miR-935 and miR-155-5p may lead to better outcomes in OSCC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Triptolide (TPL) is the most active and effective diterpene lactone epoxide compound isolated from Tripterygium. [4]. TPL has anti-inflammatory, anti-tumor, and immunologic effects on many diseases [4].…”
Section: Introductionmentioning
confidence: 99%
“…[4]. TPL has anti-inflammatory, anti-tumor, and immunologic effects on many diseases [4]. TPL inhibits the secretion of many cytokines, adhesion molecules, and chemokines and affects the functions of various cells, including dendritic cells and renal tubular epithelial cells [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…35 In addition, the miR-155-5p/SHIP1 pathway is involved in the inhibitory effect of triptolide on NF-κB activity through preformed fibril (PFF)-induced activation in microglia to decrease the release of proinflammatory cytokines. 36 Zhou et al found that in the presence of ESAT6, miR-155 was upregulated, resulting in the activation of the TLR4 signaling pathway, which could deteriorate the renal injury induced by Mycobacterium tuberculosis in mice. 12 Thus, miR-155 deficiency may inhibit the TLR4/NF-κΒ signaling pathway to exert protective effects in diseases, including CP.…”
Section: Discussionmentioning
confidence: 99%